Household savings, capital investments and public policies: What drives the German current account? - Kilian Ruppert; Nikolai Stähler (Deutsche Bundesbank, 2020)
In this article, we present a model that can account for the changes in the Germancurrent account balance since the 2000s. Our results suggest that an array of struc-tural tax and labor market reforms (Agenda 2010), population aging and pensionreforms led to an increase in the household savings rate in Germany until about2010. As domestic investment opportunities could not absorb these additional sav-ings, they were partly invested abroad. The German current account-to-GDP ratiorose. After 2010, private savings remained rather stable, but opportunities to investin Germany declined further. Our simulations suggest that a tight fiscal stance inGermany (combined with an expansionary stance in the rest of the world), under-investment in the corporate sector and productivity gains in emerging economiesafter 2010 significantly contributed to this.
Keywords: H2; J1; E43; E62; 330; Global Imbalances; Population Aging; Labor Market Reforms; Fiscal Policy; DSGE Modelling